Identification of FREM2 SNPs in Bali cattle for improving meat quality - EVA AMALIA PERTIWI; MASKUR MASKUR; TAPAUL ROZI; MUHAMMAD MUHSININ; MOKHAMAD FAKHRUL ULUM; FADHIL MUHARRAM; JAKARIA JAKARIA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Pertiwi EA, Maskur, Rozi T, Muhsinin M, Ulum MF, Muharram F, Jakaria. 2026. Identification of FREM2 SNPs in Bali cattle for improving meat quality. Biodiversitas 27 (1): d270127. https://doi.org/10.13057/biodiv/d270127. Bali cattle (Bos javanicus) are indigenous to Indonesia and valued for beef quality traits influenced by genetic variation. The FREM2 gene is recognized as one of the genetic factors that regulate marbling scores in beef cattle. This gene has been extensively studied in various livestock breeds, but has rarely been explored in local livestock breeds in Indonesia. This study aims to identify SNPs in Bali cattle as a first step in determining genetic markers to help improve meat quality, especially in Bali cattle. Blood samples were collected from 20 unrelated Bali cattle. Genomic DNA was extracted via the phenol-chloroform method. A 662 bp fragment encompassing exon 6 and intron 7 of the FREM2 gene was amplified by Polymerase Chain Reaction (PCR) and sequenced bidirectionally using Sanger technology. Sequence alignment and SNP detection were performed in MEGA X, with chromatogram inspection in FinchTV to confirm base calls. Population genetic parameters, including allele frequencies, observed and expected heterozygosity, and Polymorphic Information Content (PIC), were calculated using PopGen 3.2. Two novel SNPs were identified: g.89573C>T in exon 6, resulting in a non-synonymous Pro→Leu substitution, and g.89633G>A in intron 7. The g.89573C>T SNP deviated significantly from Hardy-Weinberg equilibrium (χ² = 4.62, p = 0.032), with observed heterozygosity (Ho = 0.50) exceeding expected heterozygosity (He = 0.455) and a PIC of 0.343. The intronic g.89633G>A variant conformed to equilibrium (p = 0.345) with a PIC of 0.269. These FREM2 markers enable marker-assisted selection to improve meat quality in Bali cattle while supporting breed conservation through genomic selection.